Համաբնագրի խոհական և հոգեբանական ընդգրկումն «Անուշ» պոեմում - Սաֆարյան, Վազգեն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В начальных вариантах поэмы доминировали обширный пейзаж, авторское слово о славном прошлом и косвенное его противопоставление фактам скованности современной жизни. Это делалось путем диалогичной активности образов. Окончательный вариант, который прошел сложный путь обработки, стал шедевром сопоставления природы и человечности, когда природа сделала целостным внутреннюю и внешнюю среду человека в противопоставлении жизни и смерти. В контексте трагичности смерти она превратилась в светлое пространство вечности героев. Ценность поэмы Ованеса Туманяна решают глубинные проявления психологии любви, которые выражаются в диалогичности героев и полифонии, а эпичность проявляется сознанием художественной меры в контексте. Vast landscapes, the author’s words about the glorious past and its indirect opposition to the facts of the constraint of modern life prevailed in the initial versions of the poem. It was portrayed by the characters’ active dialogues. The final version, which went through a difficult path of processing, became a masterpiece of juxtaposition of nature and humanity, when nature made the internal and external environment of a person integral, as opposed to life and death. In the tragic perception of death, the nature transformed it into a bright space of eternity for heroes. The value of Hovhannes Tumanyan’s poem is determined by deep manifestations of the psychology of love, which are expressed in the dialogic nature and polyphony of heroes, whereas the epic character is manifested by the sense of artistic dimension in the context.
Keywords: Բանասիրություն